2011
DOI: 10.1007/s10482-011-9667-x
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic systematics in the genomics era

Abstract: As an essential and basic biological discipline, prokaryotic systematics is entering the era of genomics. This paradigmatic shift is significant not only for understanding molecular phylogeny at the whole genome level but also in revealing the genetic or epigenetic basis that accounts for the phenotypic criteria used to classify and identify species. These developments provide an opportunity and a challenge for systematists to reanalyze the molecular mechanisms underlying the taxonomic characteristics of proka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 125 publications
1
49
0
Order By: Relevance
“…In 1999, Fitz-Gibbon and House were the first to propose that the presence or absence of genes within genomes could be used to describe taxonomic relations among prokaryotes (266). Phylogenomic studies, which are based on comparisons of orthologous genes, have demonstrated good similarity with studies based on comparisons of 16S rRNA sequences (267). In 2005, it was suggested that the average nucleotide identity (ANI) between two bacterial species could constitute an effective alternative to DNA-DNA hybridization (268,269).…”
Section: From Culturomics To Taxonogenomicsmentioning
confidence: 99%
“…In 1999, Fitz-Gibbon and House were the first to propose that the presence or absence of genes within genomes could be used to describe taxonomic relations among prokaryotes (266). Phylogenomic studies, which are based on comparisons of orthologous genes, have demonstrated good similarity with studies based on comparisons of 16S rRNA sequences (267). In 2005, it was suggested that the average nucleotide identity (ANI) between two bacterial species could constitute an effective alternative to DNA-DNA hybridization (268,269).…”
Section: From Culturomics To Taxonogenomicsmentioning
confidence: 99%
“…Genome sequences provide a tremendous, and likely the ultimate resource, for discovering the requisite types of molecular markers or characters (Gao & Gupta, 2012a;Kampfer, 2012;Nelson, Paulsen, & Fraser, 2001;Sutcliffe, Trujillo, & Goodfellow, 2012;Wolf, Rogozin, Grishin, & Koonin, 2002;Zhi, Zhao, Li, & Zhao, 2012). Comparative analyses of genome sequences are indeed leading to discovery of numerous shared-derived molecular markers (such as those Darwin had envisaged), which are providing powerful new means for understanding microbial phylogeny and systematics.…”
Section: Characteristics That Are Well-suited For Classificationmentioning
confidence: 99%
“…Whereas monoculture experimental standards and rules have guided the description of bacterial and archaeal species in the past, several colleagues have stressed that the time has come to integrate genomics as a reliable and reproducible standard into the taxonomy of the bacteria and archaea (Lan and Reeves 2000;Doolittle and Papke 2006;Fraser et al 2009;Whitman 2009;Staley 2009;Klenk and Göker 2010;Zhi et al 2012;Ellegaard et al 2013;Chun and Rainey 2014). However, simply incorporating genome sequence data into polyphasic taxonomy as proposed by Ramasamy et al (2014) might not be sufficient.…”
Section: The Failure Of Polyphasic Taxonomymentioning
confidence: 99%
“…Incorporating ecological, phylogenetic, and evolutionary dimensions is needed to define a biologically coherent species concept. Re-establishing the link between phylogenetics and taxonomy will allow a better understanding of microbial speciation (Zhi et al 2012).…”
Section: Statements Arguing In Favor Of a Genomic Microbial Taxonomymentioning
confidence: 99%